2020
DOI: 10.1101/2020.11.27.20238980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating recovery, cost, and throughput of different concentration methods for SARS-CoV-2 wastewater-based epidemiology

Abstract: As the COVID-19 pandemic continues to affect communities across the globe, the need to contain the spread of the outbreaks is of paramount importance. Wastewater monitoring of the SARS-CoV-2 virus, the causative agent responsible for COVID-19, has emerged as a promising tool for health officials to anticipate outbreaks. As interest in wastewater monitoring continues to grow and municipalities begin to implement this approach, there is a need to further identify and evaluate methods used to concentrate SARS-CoV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Our results indicate the HA filter method [30,31] combined with one-step RT-ddPCR is effective for tracking SARS-CoV-2 concentrations in wastewater influent. Similarly to reports by Altruners [17], we found the HA filter method was relatively fast and allowed an effective analysis volume for each ddPCR reaction (∼1.5 mL), which provided the needed sensitivity to quantify SARS-CoV-2 when reported cases were as low as 9 per 100,000 people in the watershed. We also found that the N1 assay was more sensitive than the N2 assay when levels were near the limits of detection, likely because of assay efficiency.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our results indicate the HA filter method [30,31] combined with one-step RT-ddPCR is effective for tracking SARS-CoV-2 concentrations in wastewater influent. Similarly to reports by Altruners [17], we found the HA filter method was relatively fast and allowed an effective analysis volume for each ddPCR reaction (∼1.5 mL), which provided the needed sensitivity to quantify SARS-CoV-2 when reported cases were as low as 9 per 100,000 people in the watershed. We also found that the N1 assay was more sensitive than the N2 assay when levels were near the limits of detection, likely because of assay efficiency.…”
Section: Discussionsupporting
confidence: 64%
“…One major challenge to implementing widespread SARS-CoV-2 wastewater surveillance is the lack of a standard method. Enveloped viruses partition between the solid and liquid phases in waste streams [16] and research is underway to evaluate concentration methods for these viruses in wastewater [17,18]. Using common controls can allow for comparison of results across different methods or laboratories [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the improved recoveries observed for BRSV after solids were removed. Despite the low and variable recovery in the current study, adsorption-extraction using electronegative membranes demonstrated reproducibility and sensitivity at reasonable cost in two previous methods comparisons 42,51 .…”
Section: Resultsmentioning
confidence: 60%
“… 15 These methods can be relatively time-consuming and become inaccessible if they are dependent on reliable supply of commercial reagents, a paucity of which has already hampered clinical SARS-CoV-2 testing efforts. 13 17 Furthermore, the use of primary concentration assumes the recovery of intact virus and is therefore not geared toward cocapturing RNA from SARS-CoV-2 viruses that have already lysed or capture of nonviral RNAs suitable as fecal concentration controls. Lastly, current CDC safety guidelines recommend a biosafety level 2 facility with unidirectional airflow and BSL-3 precautions when employing environmental sampling procedures that concentrate viruses presumed to be intact.…”
Section: Introductionmentioning
confidence: 99%